Critical thinking predicts reductions in Spanish physicians' stress levels and promotes fake news detection. (December 2021) - Escolà-Gascón, Álex; Dagnall, Neil; Gallifa, Josep
Highlights: Internists have a 30.7% higher rate of detection of fake news compared to nonscientists. Internists have accumulated clinical levels of stress since the onset of the COVID-19 pandemic. The use of critical thinking predicts more than 40% of the variance in reductions in perceived stress. Skeptical attitudes facilitate the detection of fake news in internal medicine. Abstract: The prevalence of pseudoscientific beliefs and fake news increased during the coronavirus crisis. Misinformation streams such as these potentially pose risks to people's health. Thus, knowing how these pseudoscientific beliefs and fake news impact the community of internists may be useful for improving primary care services. In this research, analyses of stress levels, effectiveness in detecting fake news, use of critical thinking (CP), and attitudes toward pseudosciences in internists during the COVID-19 crisis were performed. A total of 1129 internists participated. Several multiple regression models were applied using the forward stepwise method to determine the weight of CP and physicians' attitudes toward pseudosciences in predicting reductions in stress levels and facilitating the detection of fake news. The use of critical thinking predicted 46.9% of the reduction in stress levels. Similarly, skeptical attitudes and critical thinking predicted 56.1% of the hits on fake news detection tests. The stress levels of physicians during the coronavirus pandemic were clinically significant. The efficacy of fake news detection increases by 30.7% if the individual was a physician. Study outcomes indicate that the use of critical thinking and skeptical attitudes reduce stress levels and allow better detection of fake news. The importance of how to promote critical and skeptical attitudes in the field of medicine is discussed.